Local Ca2+ influx through CRAC channels activates temporally and spatially distinct cellular responses. - Parekh, A (2009)
Ca(2+) entry through store-operated Ca(2+) release-activated Ca(2+) (CRAC) channels controls a disparate array of key cellular responses. In this review, recent work will be described that shows local Ca(2+) influx through CRAC channels has important spatial and temporal consequences on cell function. A localized Ca(2+) rise below the plasma membrane activates, within tens of seconds, catabolic enzymes resulting in the generation of the intracellular messenger arachidonic acid and the paracrine pro-inflammatory molecule LTC(4). In addition, local Ca(2+) entry can activate gene expression, which develops over tens of minutes. Local Ca(2+) influx through CRAC channels therefore has far-reaching consequences on intra- and intercellular communication.